A Critical Analysis of Safe Abortion Road Map in Nepal - Ghimire, Jagadishwor; Maharjan, Sanju; Kattel, Pratikshya; Dangol, Deeb Shrestha; Lal, Bibek Kumar; Joshi, Nisha; Shrestha , Gauri Pradhan; Suwal, Archana; Bhattarai, Ojasbi; Shahi, Suruchi; Gautam, Manish; Bhattarai, Navaraj; et al. (Journal of Nepal Health Research Council, 2024)
Background: Abortion was legalized by the 2002 Muluki Ain to combat the surging rates of maternal mortality and morbidity. By 2021, the Maternal Mortality Rate plummeted to 151 from 539 in 1996. The decline in the abortion-related maternal mortality attributes to the implication of progressive abortion policies that includes expanded safe abortion services introduction of medical abortion, constitutional recognition of abortion, the mandates by Safe Motherhood and Reproductive Health Rights Act, and free-of-cost abortion services in government health facilities. This review study delves into exploring the contemporary abortion policies and its implications on women’s access to safe abortion services as well as the factors that affect the access. Methods: This study incorporates findings from extensive desk review of abortion services in Nepal. Results: The 2021 safe abortion services Program Implementation Guideline aims to expand safe abortion sites; however, the Nepal’s challenging geography ensues its inequitable distribution, especially in mountainous area. Policy provisions on information and financial accessibility to abortion are well navigated by the Safe Motherhood and Reproductive Health Rights Act and regulation but consistent to sporadic gaps in its implementation were comprehended in this study. This paper further discussed the Safe Motherhood and Reproductive Health Rights Act’s regressive mandate of 28-week gestational limit at any condition and the role of gender in abortion decision-making under the pretext of factors influencing safe abortion services. Conclusions: The review study recommends strategies: improving capacity for abortion services under federalism, combating stigma, improving the private sector’s readiness, and building a resilient health system. Keywords: Accessibility; availability; legalization; quality; safe abortion.